LAYANAN GO-RIDE DAN GO-FOOD DI PEKANBARU - Fahrul Indrawan; Achmad Hidir (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2019)
This research was conducted in Pekanbaru City. The purpose of this research is to know the features of services which are more profitable drivers between Go-Ride and Go-Food services. The focus topic of this research is contributing factors that drive Go-Ride and Go-Food services to the advantage. The authors use qualitative methods and use accidental sampling techniques. Data instruments are observations, interviews, polls and documentation. The study found that the more profitable feature of the Go-Jek Driver service was the Go-Ride service fiture. In research found that all active drivers perform the Go-Ride service but not for Go-Food services. What causes the Go-Ride service to provide a lot of advantages for drivers is due to fixed earnings and many points of Go-Ride service. Whereas from the Go-Food service is not at all donated a lot of points on the driver in one week. Research also finds are some of the factors that drive Go-Ride and Go-Food services to provide benefits for drivers. Consumers are limited to the accessibility and situation and condition of Customer. Each customer goal varies. These different objectives are the advantages of drivers as the farther the goal of the interbank tariff increases. Not infrequently Go-Ride services are required to make an emergency order (e.g. delivering the sick person), and not infrequently Go-Food services are requested to obtain other items that are not on the order list. However, drivers still follow the customer's wishes while within the fairness boundary. As result of Go-Ride and Go-Food service is the main choice when customer need transportation service that can answer any needs. Keywords: Go-Jek, Go-Ride, Go-Food, Social action